2008
DOI: 10.7863/jum.2008.27.10.1415
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Pulsed Ultrasound-Promoted Bone Healing Is Not Entirely Cyclooxgenase 2 Dependent

Abstract: Low-intensity pulsed ultrasound did show accelerative efficacy on bone healing. Selective inhibition of COX-2 could delay but not entirely block the benefits of LIPUS on bone healing. Low-intensity ultrasound treatment could promote bone healing through other, non-COX-2-dependent, pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…When cyclooxygenase-2 was inhibited in an in vivo bone healing model, ultrasound induced healing was delayed but did not completely cease. 28 Low intensity ultrasound is used for bone healing treatment clinically and has been reviewed in detail by e.g. Claes and Willie 29 and Malizos et al 30 Many studies have been performed to clarify the processes involved.…”
Section: Effects On Cells In Culture and Animal Modelsmentioning
confidence: 99%
“…When cyclooxygenase-2 was inhibited in an in vivo bone healing model, ultrasound induced healing was delayed but did not completely cease. 28 Low intensity ultrasound is used for bone healing treatment clinically and has been reviewed in detail by e.g. Claes and Willie 29 and Malizos et al 30 Many studies have been performed to clarify the processes involved.…”
Section: Effects On Cells In Culture and Animal Modelsmentioning
confidence: 99%
“…In recent years, the use of focused ultrasounds (FUS) has been increased in biological applications for both high intensity and low intensity modalities [1][2][3][4][5]. A high-intensity focused ultrasound is used for the rapid destruction of tissues by thermal ablation [2,3,6], for example in oncology, while low-intensity applications are based on producing midterm hyperthermia and nonthermal ultrasonic therapy [3,7], with multiple possible applications [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of focused ultrasounds (FUS) has been increased in biological applications for both high intensity and low intensity modalities [1][2][3][4][5]. A high-intensity focused ultrasound is used for the rapid destruction of tissues by thermal ablation [2,3,6], for example in oncology, while low-intensity applications are based on producing midterm hyperthermia and nonthermal ultrasonic therapy [3,7], with multiple possible applications [4,8,9]. Among the non-ablating FUS applications 2 of 15 reported in literature can be mentioned the low-intensity pulsed ultrasound (LIPUS) using focused transducers [8], drug delivery in deep tissues (as blood-brain barrier disruption) [10], gene transfer therapy [11], and sonothrombolysis [12,13], among others.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore Sena et al (2005) and Warden et al (2001) found increased levels of COX-2 which can be correlated with the mineralization process in osteoblast cultures in vitro and increased endochondral ossification in vivo (Pounder and Harrison 2008). Huang et al (2008) also demonstrated that selective inhibition of COX-2 could delay, but not inhibit the beneficial effect of LIPUS on bone healing. This suggests that LIPUS could also act via non-COX-2-dependent pathways (Huang et al 2008).…”
Section: Effect On the Cells Involved In Endochondral Ossificationmentioning
confidence: 93%
“…Huang et al (2008) also demonstrated that selective inhibition of COX-2 could delay, but not inhibit the beneficial effect of LIPUS on bone healing. This suggests that LIPUS could also act via non-COX-2-dependent pathways (Huang et al 2008). applied LIPUS on human periosteal cell culture and measured osteogenic markers such as osteocalcin and alkaline phosphatase after 2 and 4 days of ultrasound stimulation.…”
Section: Effect On the Cells Involved In Endochondral Ossificationmentioning
confidence: 93%